2022
DOI: 10.1002/hsr2.877
|View full text |Cite
|
Sign up to set email alerts
|

Kidney stones among Iranian adults: Prevalence and socioeconomic inequality assessment in a cohort‐based cross‐sectional study

Abstract: Background and Aims Kidney stone disease is a crystal concretion formed usually within the kidneys. The worldwide prevalence of kidney stones could be affected by numerous differences in socioeconomic, and environmental factors. The purpose of this study is to investigate kidney stones among Iranian adults aged between 35 and 70 years and the prevalence and evaluation of socioeconomic inequalities. Methods In this, a cohort‐based cross‐sectional study was carried out am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Previously, multiple studies have shown that older age is associated with a significantly higher probability of having had at least one episode of urolithiasis in the past. 16 , 17 Our analyses revealed a consistent finding, demonstrating an OR [95% CI] of 1.04 [1.04, 1.04] in multivariable analysis. This finding means that with every 1 year increase in age, the odds of urolithiasis increased by 4%.…”
Section: Discussionsupporting
confidence: 77%
“…Previously, multiple studies have shown that older age is associated with a significantly higher probability of having had at least one episode of urolithiasis in the past. 16 , 17 Our analyses revealed a consistent finding, demonstrating an OR [95% CI] of 1.04 [1.04, 1.04] in multivariable analysis. This finding means that with every 1 year increase in age, the odds of urolithiasis increased by 4%.…”
Section: Discussionsupporting
confidence: 77%
“…An observational study among Canadian men found no significant difference between the risk of AMH in different BMI groups 4 . In addition, a recent study among Iranian adults showed that underweight participants are at a greater risk of being diagnosed with nephrolithiasis 36 . Previous studies showed that obesity could advance prostate tissue inflammation 37 and increase the risk of cystitis and urothelial dysplasia, which in turn may cause AMH 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The PERSIAN cohort study's extensive protocol aimed to recruit participants for this study, resulting in 20,525 men and women aged 18 years and above residing in Ardabil, who participated in the baseline survey between May 2017 and February 2020. As defined in study protocol [ 26 , 27 ], the alluded age range was chosen for three reasons to be eligible in participating PERSIAN cohort: i) individuals in this age group are more likely to have well-established behaviors and lifestyles, 2) they are active and energetic enough to participate in a study; and iii) they will, within a reasonable amount of time, incur the PERSIAN study’s primary outcomes of interest (ie. a number of deaths, by cause and incidence of major NCDs) (see Poustchi et al 2017 [ 26 ] for more details).…”
Section: Methodsmentioning
confidence: 99%